2019
DOI: 10.1038/s41598-019-43069-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuralized family member NEURL1 is a ubiquitin ligase for the cGMP-specific phosphodiesterase 9A

Abstract: Neuralized functions as a positive regulator of the Notch pathway by promoting ubiquitination of Notch ligands via its E3 ligase activity, resulting in their efficient endocytosis and signaling. Using a yeast two-hybrid screen, we have identified a cGMP-hydrolysing phosphodiesterase, PDE9A, as a novel interactor and substrate of Neuralized E3 ubiquitin protein ligase 1 (NEURL1). We confirmed this interaction with co-immunoprecipitation experiments and show that both Neuralized Homology Repeat domains of NEURL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…For example, Neur regulates epithelial morphology by interacting with Stardust to down‐regulate Crumbs via endocytosis (Perez‐Mockus et al., 2017). Moreover, Neurl1 also poly‐ubiquitylates the cGMP‐specific phosphodiesterase 9A to label it for degradation (Taal et al., 2019). Mib1 is shown to bind and to ubiquitylate EPB41L5, resulting in its degradation (Matsuda et al., 2016).…”
Section: What Is the Function Of The E3 Ligases?mentioning
confidence: 99%
“…For example, Neur regulates epithelial morphology by interacting with Stardust to down‐regulate Crumbs via endocytosis (Perez‐Mockus et al., 2017). Moreover, Neurl1 also poly‐ubiquitylates the cGMP‐specific phosphodiesterase 9A to label it for degradation (Taal et al., 2019). Mib1 is shown to bind and to ubiquitylate EPB41L5, resulting in its degradation (Matsuda et al., 2016).…”
Section: What Is the Function Of The E3 Ligases?mentioning
confidence: 99%
“…This suggests that other helicases than PIF1 might remove DNA quadruplexes during S phase, whereas PIF1 may take over in DNA replication of the late origins that occurs during G2. The E3 ubiquitin‐protein ligase NEURL1B (also known as NEUR2) is involved in activation of Notch pathway during brain development in Drosophila but its function is poorly understood in vertebrates where it likely controls other processes than Notch signaling (Song et al, 2006; Taal et al, 2019). Here, we find that expression of NEURL1B is highly increased in G2 cells but its potential impact on the cell cycle progression remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that NEUR1 regulates synaptic plasticity through monoubiquitinated CPEB3, which promotes the production of AMPA receptor subunits GluA1 and GluA2 (Pavlopoulos et al, 2011). In addition, the deletion of Neur1 and Neur2 might have affected other substrates which are known to play a role in learning and memory, such as cGMP-specific phosphodiesterase 9A (Kleiman et al, 2012;Taal et al, 2019) F I G U R E 4 Reduced late long-term potentiation (L-LTP) in Neur1, 2 double knock-out mice. (a) Input-output relationships of evoked field fEPSP (fEPSP) responses at CA1 synapses for wild-type (WT) (black circles; n = 20 from 12 mice [male = 8; female = 4]), double knock-out (D-KO) (red; n = 14 from 9 mice [male = 6; female = 3]), N1-KO (yellow; n = 14 from 7 mice [male = 4; female = 3]) and N2-KO (blue; n = 11 from 7 mice [male = 4; female = 3]).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that NEUR1 regulates synaptic plasticity through monoubiquitinated CPEB3, which promotes the production of AMPA receptor subunits GluA1 and GluA2 (Pavlopoulos et al, 2011). In addition, the deletion of Neur1 and Neur2 might have affected other substrates which are known to play a role in learning and memory, such as cGMP‐specific phosphodiesterase 9A (Kleiman et al, 2012; Taal et al, 2019) and the Notch signaling pathway ligands (Brai et al, 2015; Tu et al, 2017; Wang et al, 2004). These signaling pathways have critical roles in gene transcription and de novo protein synthesis, which is also consistent with the selective impairment of L‐LTP observed in the slice physiology.…”
Section: Discussionmentioning
confidence: 99%